2022
DOI: 10.1111/bjh.18146
|View full text |Cite
|
Sign up to set email alerts
|

Immune response and adverse events after vaccination against SARS‐CoV‐2 in adult patients with transfusion‐dependent thalassaemia

Abstract: Summary Patients with transfusion‐dependent thalassaemia (TDT) are considered an at increased‐risk population for severe and/or morbid coronavirus disease 2019 (COVID‐19) infection. Timely vaccination is the main preventive method for severe COVID‐19. Different adverse events and reactions after vaccination have been reported, with severe ones being extremely rare. Patients with TDT may have altered immunity due to chronic transfusions, iron overload and chelation therapy, and splenic dysfunction. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…According to the protocol shown in Figure 1 A and Figure 2 , all the enrolled β-thalassemia patients received two doses of either the BNT162b2 (Pfizer–BioNTech) or the mRNA-1273 (Moderna) vaccines before starting with the daily intake of 2 mg of sirolimus as described by Gamberini et al [ 32 ] and by Zuccato et al [ 19 ]. The anti-SARS-CoV-2 IgG levels ( Figure 2 ) were found to be comparable to those reported elsewhere of β-thalassemia patients (not treated with sirolimus) [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 85%
“…According to the protocol shown in Figure 1 A and Figure 2 , all the enrolled β-thalassemia patients received two doses of either the BNT162b2 (Pfizer–BioNTech) or the mRNA-1273 (Moderna) vaccines before starting with the daily intake of 2 mg of sirolimus as described by Gamberini et al [ 32 ] and by Zuccato et al [ 19 ]. The anti-SARS-CoV-2 IgG levels ( Figure 2 ) were found to be comparable to those reported elsewhere of β-thalassemia patients (not treated with sirolimus) [ 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 85%
“…Delaporta et al tested the efficacy of vaccination by measuring neutralizing antibody levels in patients with thalassemia and controls. It was observed that there was a significant increase in neutralizing antibody levels at 3 and 7 weeks postvaccination, with no difference between the patient and control groups [18]. Sgherza et al performed a prospective case-control study on 65 TDT patients and compared them with 63 healthy controls for a serological response after receiving two doses of the Pfizer-BioNTech vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that patients with β-TM in general had higher anti-SARS-CoV-2 IgG antibody levels following infection or vaccination as compared to the control group. Previous studies have examined the immune responses following SARS-CoV-2 vaccination in patients with hemoglobinopathy, including thalassemia, 21 , 22 , 23 but the current study specifically concerns a cohort of patients with severely iron-overloaded, transfusion-dependent β-TM. This is interesting, as iron availability is crucial for B and T cell differentiation, 24 and iron deficiency has been associated with reduced responses to vaccines.…”
Section: Discussionmentioning
confidence: 99%